Uncovering Climate Change Education-enabling Themes in the South African Grade 7 Natural and Social Sciences School Curricula - Hebe, Headman (Jurnal Penelitian dan Pembelajaran IPA, 2024)
Environmental sustainability is perennially threatened by many challenges including drought, flooding, declining biodiversity, pollution, desertification, etcetera. Global warming, an offshoot of the greenhouse effect, is central to most of these environmental issues. Climate change education (CCE) has been touted as the main vehicle for the mitigation of climate change challenges. Accordingly, this study investigated whether the Grade 7 school curricula in South Africa provide for possible integration of CCE in pedagogy. The in-depth scoping review of the school subjects curricula taught in Grade 7 public schools classes suggests that, relative to other subjects, the Natural and Social Sciences provide greater opportunities for CCE. Accordingly, in this interpretive qualitative study, the researcher used content analysis to tease out some of the themes that could enable CCE from the Curriculum and Assessment Policy Statements (CAPS) which guide pedagogy in the two subjects. Aided by the abductive, deductive and inductive modes of extrapolation, the researcher found that there are several themes that could enable CCE in the Grade 7 Natural and Social Sciences subjects. However, the findings also suggest that there is, virtually, no guidance in the policy documents on how to infuse CCE in pedagogy. Furthermore, the literature points to the dearth of research in this area. Accordingly, the researcher recommends that the South African school curriculum be reviewed to accommodate the integration of CCE in pedagogy, and that scholars conduct more studies like this one, globally.